Acute cardiovascular response of older women to three resistance exercise protocols - Rodrigo Pereira da Silva; Jefferson da Silva Novaes; Ricardo Jacó de Oliveira; Flavio de Jesus Camilo; Martim Bottaro (Universidade Federal de Santa Catarina, 2010)
Acute cardiovascular responses to different high-velocity resistance exercise proto-cols were compared in untrained older women. Twelve apparently healthy volunteers (62.6 ± 2.9 years) performed three different protocols on the bench press (BP) and leg press (LP). All protocols consisted of three sets of 10 repetitions performed with a 10RM load and 2 min of rest between sets. The continuous protocol (CP) consisted of 10 repetitions with no pause between repetitions. The discontinuous protocols were performed with a pause of five (DP5) or 15 (DP15) seconds between the fifth and sixth repetition. Heart rate (HR), systolic blood pressure (SBP), and rate pressure product (RPP) were assessed at baseline and at the end of all exercise sets. Factorial ANOVA was used to compare the cardiovascular response among different protocols. Compared to baseline, HR, SBP and RPP were, respectively, 22.3%, 23.2% and 51.2% (p < 0.05) higher for BP exercise, and 41.7%, 43.0% and 102.9% (p < 0.05) higher for LP exercise after the third set in all protocols. For BP exercise, HR and RPP were 5.6% and 8.2% (p < 0.05) lower in DP5 and DP15, respectively, compared to CP. For LP exercise, HR, SBP and RPP were, respectively, 5.2%, 8.0% and 14.8% lower in DP5 compared to CP. In conclusion, discontinuous high-velocity resistance exercise seems to have a lower cardiovascular demand than continuous resistance exercise in older women.